Civics Teachers Ability to Apply Learning Models in Junior High Schools - Artanti Artanti (Yayasan Insan Mulia Bima, 2023)
The purpose of this research are; (1) Analyze the Civics Teacher's ability to design learning models; (2) Describe the Civics Teacher's ability to implement the learning model; (3) Analyze the factors that influence the Civics Teacher's ability to apply the learning model. Qualitative research methods. Data collection techniques were carried out by interviews, observation and documentation. Meanwhile, the data analysis technique uses data reduction, data presentation and conclusion drawing stages. The research results show that; (1) Civics Teachers' ability to plan learning models, namely; (a) consider learning objectives, so that they can be easily implemented in a structured manner; (b) Considering the suitability between the model selection and the material being taught in order to facilitate the students' understanding process; (2) The teacher's ability to use learning models, namely; (a) Discovery learning model, as a Civics learning strategy; (b) The teacher's ability to use the discovery learning model, seen in the syntax, is appropriate; (c) the discovery learning learning model is very mastered by the teacher and supported by resources; (3) The factors that influence the teacher's ability to use learning models, namely; (a) The ability of the teacher himself to use the learning model; (b) Learning objectives to be achieved; (c) Differences in students in utilizing their knowledge.